POTENSI SOSIAL EKONOMI USAHA TANI KELAPA SEBAGAI SUMBER PANGAN ALTERNATIF DI DAERAH PENYANGGA TAMAN NASIONAL UJUNG KULON ( TNUK ) - Ahmad, Bukhari (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
The results of the identification of the potential of coconut farming as an alternative food source in the buffer area of ​​Ujung Kulon National Park (TNUK). Coconut production in Sumur District is 1,181,000 grains/year and in Cimanggu District is 5,509,000. item/year. Coconut farming in the TNUK buffer area is still traditional, namely in the form of granulated coconut and is limited to producing copra products with an average production of about 1 ton of copra/ha/year and a small part of making shell charcoal. Alternative food ingredients that can be developed in the buffer zone of Ujung Kulon National Park are: Coconut sugar, coconut oil, nata de coco, coconut nira soy sauce, coconut milk, coconut cake (coconut cake), and virgin coconut oil (VCO). Factors that do not develop coconut farming in the Buffer area of ​​TNUK include technology that cannot be used, lack of product diversification.